Monitoring odour of heated extra-virgin olive oils from Arbequina and Manzanilla cultivars using an electronic nose - Messina, Valeria Marisa (2015)
It is known that fats and oils, when submitted to prolonged heat, are subjected to a series of chemical-physical modifications, generating changes in sensory and nutritional characteristics. The aim of the present research was to develop an accurate and repeatable method to predict appearance of undesired odour when extra-virgin olive oils from Arbequina and Manzanilla are submitted to heating processes, using an electronic nose. Among the metal oxide sensor response (electronic nose) an odour index was performed. Emissions of several volatile organic compounds released during the process were analysed by SPME-Gas chromatography. Linear discriminant analysis was applied on the sensor response; it was found that among eight sensors, four sensors were more specific for detecting release of volatile organic compounds during the heating process. The Mahalanobis distance method was adopted to create an odour index and was correlated with emissions of n-pentanal, n-hexanal, n-heptanal and n-nonanal. Data showed that the methodology accurately and rapidly predicted changes in odour pattern between cultivars.